Second Five Year Plan (1956-57 to 1960-61) Aurangabad District Bombay State - Planning Commission (Planning Commission, 1958)
Aurangabad district, which formed a part of the former Hyderabad State, is now integrated with the new Bombay State and with the four districts of Bhir, Nanded, Parbhani and Osmana- bad constitutes what is known as the Marathwada region. It has East Khandesh District on the north, Bhir and Ahmednagar districts on the south, Buldhana and Parbhani districts on the east and Nasik district on the west. the area of the district is 6318 sq. miles with a population of 11,79,404. For administrative purposes the eleven talukas and one mahal of the district have been grouped into two divisions, as indicated below
Bombay State